Job satisfaction and co-worker wages: status or signal? - Andrew E. Clark; Nicolai Kristensen; Niels Christian Westergård-Nielsen (Institute for the Study of Labor (IZA), 2007)
This paper uses matched employer-employee panel data to show that individual job satisfaction is higher when other workers in the same establishment are better-paid. This runs contrary to a large literature which has found evidence of income comparisons in subjective well-being. We argue that the difference hinges on the nature of the reference group. We here use co-workers. Their wages not only induce jealousy, but also provide a signal about the worker's own future earnings. Our positive estimated coefficient on others' wages shows that this positive future earnings signal outweighs any negative status effect. This phenomenon is stronger for men, and in the private sector.
Keywords: 330; Job satisfaction; co-workers; comparison income; wage expectations; tournaments; Arbeitszufriedenheit; Gruppenarbeit; Lohnstruktur; Erwerbsstatus; Signalling; Vergleich; Leistungsmotivation; Dänemark